Fabrication of metallic implants using palm based binder through MIM process - Omar, Mohd Afian; Noorsal, Kamariah; Subuki, Istikamah; Abdullah, Norsyakira; Zulkifly, Ahmad Hafiz (EPMA European powder metallurgy assiosiation, 2011)
Metal Injection moulding (MIM) is an advanced near net shape forming process for high quality of complex shapes combined with high properties of materials. For economic reasons, it is necessary to have demand for a large quantity of parts. This paper presents the attempt to manufacture metallic implants particularly fracture fixation plates for orthopedic applications for commercial purposes by MIM process using newly developed palm based binder system. The stainless steel powder with the median particle size of 16 μm and a binder consisting of major fraction of palm stearin and a minor fraction of polyethylene were mixed at 160°C using a sigma-blade mixer for one hour to prepare the feedstock of the fracture fixation plates. The fracture fixation plates component was injection moulded using 80 ton metal injection moulding machine with the nozzle temperature of 200°C. Prior to sintering, the specimens were debound using a combination of solvent extraction and thermal pyrolysis method. The specimens were then sintered under vacuum. The properties of the fracture fixation plates such as physical appearance and densities were presented and discussed. Furthermore, the in vitro biocompatibility study on the fracture plates produced also been carried out.